Anemia, hematinic deficiencies, and hyperhomocysteinemia in serum gastric parietal cell antibody-positive burning mouth syndrome patients without serum thyroid autoantibodies - Ying-Tai Jin; Yu-Hsueh Wu; Yang-Che Wu; Julia Yu-Fong Chang; Chun-Pin Chiang; Andy Sun (Elsevier, 2021)
Background/purpose: Our previous study found that 70 of 884 burning mouth syndrome (BMS) patients have serum gastric parietal cell antibody (GPCA) positivity but without thyroglobulin antibody (TGA) and thyroid microsomal antibody (TMA) (so-called GPCA+TGAˉTMAˉBMS patients). This study assessed whether these 70 GPCA+TGAˉTMAˉBMS patients had significantly higher frequencies of macrocytosis, anemia, hematinic deficiencies, and hyperhomocysteinemia than 553 GPCA-negative, TGA-negative, and TMA-negative BMS (GPCAˉTGAˉTMAˉBMS) patients or 442 healthy control subjects. Materials and methods: Complete blood count, serum iron, vitamin B12, folic acid, homocysteine, GPCA, TGA, and TMA levels in 70 GPCA+TGAˉTMAˉBMS patients, 553 GPCAˉTGAˉTMAˉBMS patients, and 442 healthy control subjects were measured and compared. Results: We found that 15.7%, 28.6%, 20.0%, 11.4%, 2.9%, and 25.7% of 70 GPCA+TGAˉTMAˉBMS patients and 3.8%, 17.7%, 15.9%, 3.8%, 2.7%, and 20.1% of 553 GPCAˉTGAˉTMAˉBMS patients had macrocytosis, blood hemoglobin, iron, vitamin B12, and folic acid deficiencies, and hyperhomocysteinemia, respectively. Moreover, both 70 GPCA+TGAˉTMAˉBMS patients and 553 GPCAˉTGAˉTMAˉBMS patients had significantly greater frequencies of macrocytosis, blood hemoglobin, serum iron, vitamin B12, and folic acid deficiencies, and hyperhomocysteinemia than 442 healthy control subjects (all P-values < 0.05). In addition, 70 GPCA+TGAˉTMAˉBMS patients also had greater frequencies of macrocytosis, anemia, serum vitamin B12 deficiency, and hyperhomocysteinemia than 553 GPCAˉTGAˉTMAˉBMS patients (all P-values < 0.05). Conclusion: The GPCA + TGAˉTMAˉBMS patients have significantly greater frequencies of macrocytosis, anemia, serum iron, vitamin B12, and folic acid deficiencies, and hyperhomocysteinemia than healthy control subjects and significantly greater frequencies of macrocytosis, anemia, serum vitamin B12 deficiency, and hyperhomocysteinemia than GPCAˉTGAˉTMAˉBMS patients.